2022
DOI: 10.3390/nu14142908
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Sodium Content in 4082 Kinds of Commercial Foods in China

Abstract: High-sodium intake is associated with the increased risk of hypertension and cardiovascular disease. Monitoring and analyzing the sodium content in commercial food is instructive for reducing sodium intake in the general population. The sodium content of 4082 commercial foods across 12 food groups and 41 food categories was collected and analyzed, including 4030 pre-packaged foods and 52 artisanal foods. The food group with the highest average sodium content (6888.6 mg/100 g) contained sauces, dressings, sprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Hao et al collected 4030 pre-packaged and 52 artisanal food products in China and evaluated their sodium content. 84 They found that 33.72% of the products met the low-sodium standard and 37.30% reached the high-sodium standard. Due to higher production costs, weak growth, and intense competition, there may not be enough incentive for companies to voluntarily undertake sodium reduction in later stages.…”
Section: Dietary Behavior Changesmentioning
confidence: 98%
See 1 more Smart Citation
“…Hao et al collected 4030 pre-packaged and 52 artisanal food products in China and evaluated their sodium content. 84 They found that 33.72% of the products met the low-sodium standard and 37.30% reached the high-sodium standard. Due to higher production costs, weak growth, and intense competition, there may not be enough incentive for companies to voluntarily undertake sodium reduction in later stages.…”
Section: Dietary Behavior Changesmentioning
confidence: 98%
“…8A. The top 10 keywords, identified based on the frequency of occurrence after eliminating search qualifiers from the literature, include hypertension (339), cardiovascular disease (121), health (96), consumption (90), foods (84), urinary sodium (82), excretion (77), meta-analysis (75), disease (75), and risk (73). Based on the keyword overlay time view (Fig.…”
Section: Keyword Co-occurrence Analysismentioning
confidence: 99%
“…Statement from Devanthi and Gkatzionis [4] shows that a high concentration of salt in brine will subdue the growth of spoilage and pathogenic microorganisms and provide favorable conditions for halotolerant microorganisms involved in the formation of soy sauce's flavor. Moreover, Hao et al [60] stated that sodium chloride, combined continuously and synergistically with other characteristic umami tastes (glutamic acid), will improve the taste of soy sauce. The concentration of sodium chloride found in this research was substantially lower than that found in other investigations.…”
Section: B Analysis Of Chemical Properties In Naturally Brewed Soy Saucementioning
confidence: 99%
“…High dietary salt intake remains a big challenge as many people in various populations around the world are still unable to stop consuming high amounts of salt due to the diverse sources of dietary salt available in common foods [ 126 , 127 , 128 ]. It is therefore understandable that efforts are being made to find alternative ways of overcoming the deleterious effects of high salt overload on human health, other than simply advising people to reduce salt intake.…”
Section: Glycocalyx and Salt Interactionsmentioning
confidence: 99%